A Neglected Classic in the Theory of Distribution - Whitaker, John K. (Journal of Political Economy, 1982)
In 1873 there appeared in Danish an essay by two Danish mathematicians, Frederik Bing and Julius Petersen. This essay has received almost no attention, yet it appears on close inspection to be a strikingly original and path-breaking contribution to neoclassical distribution theory. A detailed exposition of the authors' theory and some of their applications is presented in the light of an interpretive model expressed in modern terms. A concluding section gives some information about the authors and attempts to assess their contribution and its claims to a significant place in the history of economic analysis.